Competitiveness of Vietnam’s Financial Institutions in the Global Financial Market: The case of Vietnam’s Commercial Banks - Nguyen, Thanh Phong (University of Economics Ho Chi Minh City, 2023)
Using panel data collected from financial statements of 28 commercial banks in Vietnam, this paper investigates their competitiveness through an analysis of such a few elements as bank size, technological level, human resources quality, and managerial level. For a more objective evaluation the paper employs the Panzar–Rosse (P–R) model along with the use of some common econometrical techniques like Pooled OLS, FEM, REM, GLS, and H-statistic. The results show that the overall competitiveness of these banks is higher, compared to the pre-crisis period of 2008–2009. The monopolistic competition among them are also found, together with certain improvements in bank competitiveness, observed through increased bank size, enhanced human resources quality, better technological advances, and higher levels of managerial skills in compliance with international standards.